The Palaeoproterozoic anatomy of the Lewisian Complex, NW Scotland: evidence for two ‘Laxfordian’ tectonothermal cycles - Andrew J. Mason (2016)
A new structural examination of Palaeoproterozoic high- P granulites on South Harris, NW Scotland, when integrated with previous geochronological, structural and metamorphic studies on key areas of the Lewisian Complex, suggests the existence of two distinct tectonothermal cycles within the Palaeoproterozoic ‘Laxfordian Event’, which on South Harris are separated by a >100 myr hiatus in deformation. The older cycle, from c . 1.91 to 1.85 Ga, records the development of an active continental margin on the Archaean gneisses that dominate the Complex, and the subsequent onset of continent–continent collision; this represents the continuation of the Nagssugtoqidian orogen of Greenland. Evidence for this is concentrated in allochthonous slivers of the former active continental margin displaced during the younger cycle. The younger cycle, around 1.75–1.65 Ga, began with thrust-related crustal thickening that initiated regionally extensive amphibolite-facies metamorphism and ductile deformation, which dominates the preserved ‘Laxfordian’ deformation history. This may be the peripheral expression of the accretion of the Malin block to the SW of the Lewisian, and represents the lateral continuation of the Labradorian–Ketilidian orogen of North America.